Positive and negative triangularity in RFX-mod2: a comparative analysis. (1st June 2022) - Predebon, I.; Abate, D.; Pigatto, L.
Abstract: We present a comparative analysis of practically achievable positive and negative triangularity configurations in the next RFX-mod2 tokamak campaign. The designed single-null positive triangularity plasmas—based on analogous, formerly realized scenarios in RFX-mod—are mirrored, keeping most of the other parameters fixed. In this procedure, we show how some local and global geometric properties of the plasma are modified, and how these properties reflect on changes in vertical stability, low- n ideal stability and electrostatic turbulence level.